Miskonsepsi Strict Parent Pada Anak Perempuan Jawa - Handayani, Dewi Rosya Wahyu (Universitas Sarjanawiyata Tamansiswa, 2024)
This article examines misconceptions about strict parenting practices for girls in Javanese culture. These misconceptions often lead to misunderstandings and conflicts between generations, especially between parents and daughters. Strict parenting practices in Javanese culture are intended to protect girls and maintain family honor. This study aims to investigate misconceptions about strict parenting practices for Javanese girls and reveal the implications of these misconceptions on parent-child relationships and their impact on child development in the context of Javanese culture. This study uses qualitative methods and Clifford Geertz's cultural interpretation theory, with primary data from interviews with Javanese girls from educational and artistic families, and secondary data from literature studies. Data analysis was conducted using a descriptive interpretive approach to understand the perceptions and experiences of informants related to strict parenting patterns. The results show that these misconceptions are caused by differences in interpretation between generations, lack of information about Javanese cultural values, and the influence of media. This article proposes a deeper understanding to develop a more appropriate parenting approach to reduce the negative impacts of these misconceptions.